ANALYSIS OF MSMEs DEVELOPMENT THROUGH CAPITAL, QUALITY OF HUMAN RESOURCES, AND MENTALITY OF BUSINESS ACTORS - Anis Lelimawarti; Moh. Afrizal Miradji; Soffia Pudji Estiasih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
MSMEs development needs to be carried out because it is related to their contribution to the national economy. The development of MSMEs cannot be separated from indicators of increasing income, the addition of various types of businesses, and larger business scales. Of course, it is related to problems, capital, quality of human resources, and the mentality of business actors in running the business. The aim of this research is to analyze the development of MSMEs through capital issues, quality of human resources and the mentality of business actors so that consistency in research results can be found so that they can be used as a basis for developing MSMEs in general. The sampling technique in this research used accidental sampling. The data collection technique uses a survey via questionnaire with 100 respondents divided according to the proportion of the number of MSMEs in each region. Analysis uses Path as data analysis with Smart-PLS as the analysis tool. The findings of this research show that capital and the quality of human resources influence the development of MSMEs, while the mentality of business actors has no influence on the development of MSMEs.